In silico design of novel precision vaccine targeting sclerostin epitopes for osteoporosis prevention and treatment - Luo, Jianzhou; Wu, Tailin; Guan, Bin; Li, Lin; Yang, Zili; Tao, Huiren (Frontiers in Immunology, 2025)
BackgroundOsteoporosis has become an increasingly pressing global public health challenge. Monoclonal antibody romosozumab (ROMO), which targets sclerostin (SOST), a critical inhibitor of bone formation, demonstrates considerable therapeutic efficacy. However, its relatively high cost and potential cardiovascular risks may hinder broader clinical application. Current preventive measures remain inadequate.MethodsThis study presents a novel, cost-effective osteoporosis vaccine with dual preventive and therapeutic capabilities, derived from the high-affinity binding epitope of ROMO to SOST. ELISA screening determined that the SOST131–163 region within loop3 domain serves as the primary epitope for ROMO, suggesting a role in skeletal regulation with minimal impact on cardiovascular system. SOST131–163 was conjugated to the diphtheria toxin translocation domain (DTT) to create novel SOST-targeted vaccines.ResultsImmunogenicity assays demonstrated that both DDT-SOST(131-163)3 (DS3) and DDT-SOST(131-163)5 (DS5) elicited strong IgG2 antibody responses comparable to ROMO. Molecular docking studies indicated strong affinities of DS3 and DS5 for Toll-like receptor 2 (TLR2), enhancing TLR2-mediated humoral B-cell immunity and eliciting synergistic T-helper cell responses. Recombinant expression in Escherichia coli confirmed the successful production of DS3 and DS5, with molecular weights of 31.8 kDa and 40.3 kDa, respectively. In vivo experiments showed that the vaccines effectively induced high-titer anti-SOST antibodies in mice, overcoming immune tolerance. Additionally, cell-based assays indicated that antiserum from vaccinated mice inhibited osteoclast differentiation and promoted osteoblast mineralization.ConclusionThe SOST-targeted vaccination strategy offers a promising and cost-effective approach for the early prevention and sustained management of osteoporosis, demonstrating substantial potential for clinical translation.